Impact of environmentally friendly processing solvents on the properties of blade‐coated polymer solar cells. Issue 4 (23rd November 2018) - Bouzid, Hamza; Prosa, Mario; Bolognesi, Margherita; Chehata, Nadia; Gedefaw, Desta; Albonetti, Cristiano; Andersson, Mats R.; Muccini, Michele; Bouazizi, Abdelaziz; Seri, Mirko
ABSTRACT: High‐performance polymer solar cells (PSCs) are typically fabricated by spin coating in inert atmosphere from toxic halogenated solvents such as 1, 2‐dichlorobenzene ( o ‐DCB) and chlorobenzene. This fabrication process is potentially hazardous for both the humans and the environment and dramatically impacts the possibility for the organic photovoltaic technology to be adopted at large scale. In this work, efficient PSCs blade coated in air using nonhalogenated 1, 2, 4‐trimethylbenzene (TMB) as processing solvent are demonstrated. The active layer, based on a previously synthesized benchmark polymer PFQ2T‐benzodithiophene blended with [6, 6]‐phenyl‐C61‐butyric acid methyl ester (PC61 BM), showed an enhanced solid‐state aggregation induced by the use of TMB. Compared to o ‐DCB‐processed devices, the solar cells fabricated from TMB resulted 10% more efficient with a power conversion efficiency of 4.20%. Interestingly, the improved photovoltaic performance resulted from the combination of synergic effects promoted by a more favorable film morphology, such as high exciton dissociation efficiency and lower bimolecular recombinations resulting in higher charge collection efficiency at the electrodes. The positive effect of TMB, compared to that of commonly employed halogenated solvents, confirms the great potential of this approach for the development of efficient PSCs for practical applications with reduced environmental impact. © 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2019, 57, 487–494 Abstract : By replacing a common (hazardous) halogenated solvent with a nonchlorinated one, blade‐coated bulk heterojunction solar cells with ~10% improved PCEs were prepared. For an in depth understanding of the observed enhancement and to disclose the effects induced by the halogen‐free solvent, the optical, morphological, and electrical properties, with particular attention to the internal device mechanisms such as charge generation, recombination, and collection were carefully investigated.